Trends in application of Green Star SA credits in South African green building - Hoffman, Danie; Huang, Ling-Yi; van Rensburg, Jean; Yorke-Hart, Amy (Acta Structilia, 2020)
The South African green building industry is growing towards maturity. Stakeholders need to observe, document, and be informed about trends and development of the industry. This article evaluates whether application trends have emerged of often achieved and seldom achieved Green Star SA credits by all new office buildings that received a Green Star SA rating between 2009 and 2015 in South Africa. Any observed trends are further described by aspects such as the categories of the Green Star SA tool and the Green Star SA rating achieved. The article considers the data of 95 office buildings, made available by the Green Building Council of South Africa (GBCSA). A quantatitive research approach is used to investigate the use frequency of every credit in the Green Star SA tool and to identify trends in credit use. The study finds that 21 of the 67 credits are achieved on average by >80% of the certified projects. Another 14 credits have an average achievement rate of <20%. The nine categories of the Green Star SA tool also varies from average achievements of 84% for Water to only 19% for Innovation. The Green Star SA rating level is also found to be positively correlated to often used credits and negatively correlated to seldom used credits. This article observes industry-wide trends with the potential to negatively affect the ability of green buildings to deliver the required sustainability outcomes expected of them. This finding and the potential outcome thereof need to be monitored and managed by stakeholders such as the GBCSA.